Drug-induced movement disorders - Duma, Stephen R (Aust Prescr, 2019)
Many therapeutic and illicit drugs can cause movement disorders. Antipsychotics and antiemetics are most commonly implicated The time of onset of the movement disorder may be acute, subacute, or chronic. The severity can range from mild to severe and life-threatening Early recognition of a drug-induced movement disorder is essential to allow for prompt intervention. This includes stopping the offending drug, supportive care, and sometimes other pharmacological treatment